Detecting common facial features in static images - Lau, Weng Keong; Tay, Peter Cheng Yen; Woon, Yun Keong (Universiti Malaysia Sarawak, (UNIMAS), 2004)
The digital world is embarking on a greater challenge to create a better place to live in, provide as many assistants to humankind at completing everyday task faster and, trouble-free. Image processing is becoming increasingly important when it comes to high technology era. The human face is an important recognition area to identify a person which puts into practice applications such as human face recognition, facial expression analysis, surveillance systems and video-conferencing. This project is entitled "Detecting common facial features in static images". The prototyped system will be able to detect highlighted face in an image using mouse click and drag. From the highlighted face, the system will locate the individual's facial features such as the eyes, the nose and the mouth. The prototyped system could detect facial features that are on still upright frontal images of a person who is looking straight ahead. The static images are in Joint Photographic Experts Group (JPEG) format taken from the internet, digital camera, archives and scanner. The method used for the proposed system is greyscale thresholding based on model based method. The prototyped system uses Java programming and implements Java APL